Chemical sensors based on N-substituted polyaniline derivatives: reactivity and adsorption studies via electronic structure calculations - Mandú, Larissa O. [UNESP]; Batagin-Neto, Augusto [UNESP] (Springer Nature, 2018)
Conjugated organic polymers represent an important class of materials for varied technological applications including in active layers of chemical sensors. In this context, polyaniline (PANI) derivatives are promising candidates, mainly due to their high chemical stability, good processability, versatility of synthesis, polymerization, and doping, as well as relative low cost. In this study, electronic structure calculations were carried out for varied N-substituted PANI derivatives in order to investigate the potential sensory properties of these materials. The opto-electronic properties of nine distinct compounds were evaluated and discussed in terms of the employed substituents. Preliminary reactivity studies were performed in order to identify adsorption centers on the oligomer structures via condensed-to-atoms Fukui indexes (CAFI). Finally, adsorption studies were carried out for selected derivatives considering five distinct gaseous analytes. The influence of the analytes on the oligomer properties were investigated via the evaluation of average binding energies and changes on the structural features, optical absorption spectra, frontier orbitals distribution, and total density of states in relation to the isolated oligomers. The obtained results indicate the derivatives PANI-NO2 and PANI-C6H5 as promising materials for the development of improved chemical sensors.
Keywords: Adsorption study; Chemical sensors; Electronic structure calculations; N-substituted polyaniline derivatives; Reactivity indexes